Therapeutic Effect of the Mitochondria-Targeted Antioxidant SkQ1 on the Culture Model of Multiple Sclerosis. (1st July 2019) - Fetisova, Elena K.; Muntyan, Maria S.; Lyamzaev, Konstantin G.; Chernyak, Boris V.
Abstract : Multiple sclerosis (MS) is a heterogeneous autoimmune disease of unknown etiology characterized by inflammation, demyelination, and axonal degeneration that affects both the white and gray matter of CNS. Recent large-scale epidemiological and genomic studies identified several genetic and environmental risk factors for the disease. Among them are environmental factors of infectious origin, possibly causing MS, which include Epstein-Barr virus infection, reactivation of some endogenous retrovirus groups, and infection by pathogenic bacteria (mycobacteria, Chlamydia pneumoniae, and Helicobacter pylori ). However, the nature of the events leading to the activation of immune cells in MS is mostly unknown and there is no effective therapy against the disease. Amazingly, whatever the cause of the disease, signs of damage to the nerve tissue with MS lesions were the same as with infectious leprosy, while in the latter case nitrozooxidative stress was suggested as the main cause of the nerve damage. With this in mind and following the hypothesis that excessive production of mitochondrial reactive oxygen species critically contributes to MS pathogenesis, we studied the effect of mitochondria-targeted antioxidant SkQ1 in an in vitro MS model of the primary oligodendrocyte culture of the cerebellum, challenged with lipopolysaccharide (LPS). SkQ1 was found to accumulate in the mitochondria of oligodendrocytes and microglial cells, and it was also found to prevent LPS-induced inhibition of myelin production in oligodendrocytes. The results implicate that mitochondria-targeted antioxidants could be promising candidates as components of a combined therapy for MS and related neurological disorders.